The META-ANALISIS PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPA DAN KEMAMPUAN BERPIKIR KREATIF - Syamsul Bahari (Physics and Science Education Journal (PSEJ), 2025)
The project-based learning model is a new learning model where students actively participate in creating knowledge independently through their friends in groups and completing projects designed by the teacher. The aim of this research is to determine the effect of the project-based learning model on science learning outcomes. This research uses a literature review method. A meta-analysis is a study that looks at similar articles. The data collection technique is to collect articles about the influence of project-based learning models on science learning outcomes. The articles used in this research were 21 articles related to this topic. The results of this research show that the PJBL model has a significant influence on learning outcomes in science subjects with an average effect size of 2.31. The Project Based learning model influences science learning outcomes. The use of the Project Based Learning Model influences science learning outcomes, this is in accordance with the calculation results with an average effect size of 2.31. PJBL, using this learning model can make it easier for students to absorb and understand the material provided by the teacher. Project based learning is a learning model that can improve science learning outcomes and creative thinking abilities.